Morphological changes in peripheral nerves after neurosuture and electrical stimulation. - Tsymbaliuk, Y. V.; Malisheva, T. A.; Rudenko, S. O.; Vaslovich, V. V. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. Traumatic injuries of peripheral nerves leads to profound disability and 40%, while plexus injury or damage to multiple nerves-stage reaches 76%. Finding ways to increase the effectiveness of rehabilitation treatment of patients with peripheral nerve injury consequences, given the substantial progress microsurgical reconstructive surgery, imperative. Objective. The aim was to study the morphological changes of peripheral nerves after neurosuture under influence of electrical stimulation at different time periods. Methods.Morphological plain and special and histochemical methods were used. The features of blood supply of peripheral nerve reconstruction were quantified by neurovasal quotient. Qualitative and quantitative regeneration of the sciatic nerve of rabbits that were exposed to electrical stimulation and comparison groups were analyzed. Results and Conclusion. Excessive development of connective tissue and little amount of vascular zones were found within the formation of neuroma without electrical stimulation. Study of long-term electrical stimulation on sciatic nerve regeneration after neurosuture (in rabbits) showed structural changes, indicating a speed-up and restoration of physiological conditions of the structure of nerve trunks during the experiment. The positive impact of electrical vector (in both qualitative and quantitative criteria) on signs of regeneration in nerve trunks in research groups towards comparison group was stated. Regenerative changes in electrical stimulation occur as dynamic newgrowth of stroma of nerve trunk (especially peryneurium cells) in the area of neuroma. These studies prove compensatory-adaptive (reparative) effect of prolonged electrical stimulation with the recovery of functionally capable structures of nerve fibers (remyelo- and stromal-angioregeneration).